Measurement of tidal breathing flows in infants using impedance pneumography. Issue 2 (16th February 2017) - Malmberg, Leo Pekka; Seppä, Ville-Pekka; Kotaniemi-Syrjänen, Anne; Malmström, Kristiina; Kajosaari, Merja; Pelkonen, Anna S.; Viik, Jari; Mäkelä, Mika J.
Tidal breathing flow volume (TBFV) profiles have been used to characterise altered lung function. Impedance pneumography (IP) is a novel option for assessing TBFV curves noninvasively. The aim of this study was to extend the application of IP for infants and to estimate the agreement between IP and direct pneumotachograph (PNT) measurements in assessing tidal airflow and flow-derived indices. Tidal flow profiles were recorded for 1 min simultaneously with PNT and uncalibrated IP at baseline in 44 symptomatic infants, and after methacholine-induced bronchoconstriction in a subgroup (n=20). The agreement expressed as the mean deviation from linearity ranged between 3.9 and 4.3% of tidal peak inspiratory flow, but was associated with specific airway conductance (p=0.002) and maximal flow at functional residual capacity ( V′ maxFRC ) (p=0.004) at baseline. Acute bronchoconstriction induced by methacholine did not significantly affect the agreement of IP with PNT. TBFV indices derived from IP were slightly underestimated compared to PNT, but were equally well repeatable and associated with baseline V′ maxFRC (p=0.012 and p=0.013, respectively). TBFV profiles were consistent between IP and PNT in most infants, but the agreement was affected by reduced lung function. TBFV parameters were not interchangeable between IP and PNT, but had a similar association with lung function in infants. Impedance pneumography is a novel noninvasive option for tidal flow profile and lung function monitoring in infants http://ow.ly/7RId305Oj80